IMPLEMENTASI PERANAN SEKRETARIS DALAM MEWUJUDKAN EFISIENSI KERJA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) PEMERINTAHAN KABUPATEN BADUNG - Ni Putu Pradnyani Wulandari; Ida Bagus Ngurah Wimpascima; Ni Nyoman Menuh; Nyoman Parta (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2023)
In the current era of globalization, leaders in various agencies, both government and private sectors, are faced with challenges and fierce competition. They have various obligations and duties in carrying out their daily work, so they need a secretary to support their duties more efficiently and effectively. The aim of this research is to understand how secretaries contribute to improving work efficiency in the office environment of the Investment and One-Stop Integrated Services Service. Qualitative data analysis method by analyzing data that has been collected well. The research results show that a secretary must have a high desire to carry out work effectively and efficiently so that it will be easier for the secretary to complete his work on time. In realizing the work efficiency of secretaries at the One Stop Integrated Services and Investment Service (DPMPTSP) by implementing several factors such as the form of implementing SOPs, BIMTEK which have been implemented and are also influenced by discussions and communication between workers.